The Impact of Lipoproteins on Wound Healing: Topical HDL Therapy Corrects Delayed Wound Healing in Apolipoprotein E Deficient Mice - Stephanie C. Gordts; Ilayaraja Muthuramu; Ruhul Amin; Frank Jacobs; Bart De Geest (MDPI AG, 2014)
Chronic non-healing wounds lead to considerable morbidity and mortality. Pleiotropic effects of high density lipoproteins (HDL) may beneficially affect wound healing. The objectives of this murine study were: (1) to investigate the hypothesis that hypercholesterolemia induces impaired wound healing and (2) to study the effect of topical HDL administration in a model of delayed wound healing. A circular full thickness wound was created on the back of each mouse. A silicone splint was used to counteract wound contraction. Coverage of the wound by granulation tissue and by epithelium was quantified every 2 days. Re-epithelialization from day 0 till day 10 was unexpectedly increased by 21.3% (p < 0.05) in C57BL/6 low density lipoprotein (LDLr) deficient mice with severe hypercholesterolemia (489 ± 14 mg/dL) compared to C57BL/6 mice and this effect was entirely abrogated following cholesterol lowering adenoviral LDLr gene transfer. In contrast, re-epithelialization in hypercholesterolemic (434 ± 16 mg/dL) C57BL/6 apolipoprotein (apo) E−/− mice was 22.6% (p < 0.0001) lower than in C57BL/6 mice. Topical HDL gel administered every 2 days increased re-epithelialization by 25.7% (p < 0.01) in apo E−/− mice. In conclusion, topical HDL application is an innovative therapeutic strategy that corrects impaired wound healing in apo E−/− mice.